Odpowiedź :
Odpowiedź:
A
4x +2y - 1 = 0
2y = - 4x + 1
y = (- 4/2)x + 1/2
y = - 2x + 1/2
B.
3/2x - 1/4 - 1 = 0
- 1/4y = - 3/2x + 1 | * (- 4)
y = (- 3/2) * (- 4)x - 4
y = 6x - 4
y = ax + b - postać kierunkowa prostej
gdzie:
a - współczynnik kierunkowy
b - wyraz wolny
[tex]A.\\4x+2y - 1 = 0\\\\2y = -4x+1 \ \ \ |:2\\\\\boxed{y = -2x+\frac{1}{2}} \ - \ postac \ kierunkowa[/tex]
[tex]B.\\\frac{3}{2}x - \frac{1}{4}y - 1 = 0 \ \ \ |\cdot(-4)\\\\-6x+y+4 = 0\\\\\boxed{y = 6x-4} \ - \ postac \ kierunkowa[/tex]